Time course changes of the kinematics and kinetics during double-poling technique in cross-country sprint skiing - Fujita, Z.; Ishige, Y.; Yoshioka, S.; Tauchi, K.; Tsuchiya, J. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Ten years ago, sprint skiing events were introduced into the World Ski Championships, and subsequently, some skiers have tried to adapt their cross-country skiing technique to the higher racing speeds attained during sprint skiing. The racing speed using the double-poling technique is high, and many athletes use double-poling technique when they want to accelerate or when they are close to the finish line (Stöggl, et al., 2006). Thus, it is important that athletes keep the high level of the racing speed. However, no study could be found elucidating a relationship between the racing speed and the time course changes of kinematics and kinetics during double-poling technique. The purpose of this study was to examine time course changes of the kinematics and the kinetics during double poling techniques in cross-country sprint skiing.